2016
DOI: 10.23917/ppd.v3i1.2715
|View full text |Cite
|
Sign up to set email alerts
|

Keefektivan Metode Learning Starts With a Question Pada Pembelajaran Geometri

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…This result is in accordance with the research of Parmithi and Wahidin [8] who found that the use of the LSQ model can improve student learning achievement. Pradana [16] suggested that the LSQ model is able to provide active learning so that learning outcomes are better. This is because the process and steps of the LSQ model can lead students to be ready to learn.…”
Section: Results Of Data Analysis To Test Long Term Memory Variablesmentioning
confidence: 99%
“…This result is in accordance with the research of Parmithi and Wahidin [8] who found that the use of the LSQ model can improve student learning achievement. Pradana [16] suggested that the LSQ model is able to provide active learning so that learning outcomes are better. This is because the process and steps of the LSQ model can lead students to be ready to learn.…”
Section: Results Of Data Analysis To Test Long Term Memory Variablesmentioning
confidence: 99%